Hubungan Antara Job demands Dengan Workplace Well-being Pada Pekerja Shift - Anwarsyah, Wanda Irawan; Salendu, Alice; Radikun, Tulus Budi Sulistyo (Jurnal Psikologi: PITUTUR, 2012)
This  study  focused  on  the  relationship  between job  demands withworkplace well-being on shift workers  in  a  company  engaged  inmanufacturing  plastic  packaging  production.  Previous  research  has  not much  to  explain  the  relationship  between  two  variables,  especially  in Indonesia,  and  its  application  in shift workers. Workplace well-being is defined as a sense of prosperity gained workers from their jobs, as measured through  the Workplace Well-being Index  (WWBI)  (Page,  2005). Job demands,  which  is  explained  by  the  type  of quantitative  demands in  this study, is defined as something that relates directly to the amount of work to be done and a major source of stress (Kristensen, Bjorner, Christensen, & Borg, 2004), as measured by quantitative questionnaires job demands in the Indonesian Quality of Work Life Questionnaire (IQWiQ) (Radikun, 2010). The  sample  in  this  study  included  155 shift workers  using  accidentalsampling. The analysis showed that there was a Significant  negative  relationship  between job  demands with workplace well-being on shift workers (r = -0221, p <0.05, one-tailed). From the  research,  companies  are  advised  to  review  the  current  number  of workers with production targets that must be produced, an appreciation ofthe performance of workers and wages.